Effect of treatment of low carbon steel tensile test specimen on tensile strength for tractor wheel axle - Karyanik, Karyanik (Protech Biosystems Journal, 2023)
This study aims to determine the tensile strength of low carbon steel material specimens against the influence of specimen treatment. The method used in the research is an experimental method using a Universal Testing Machine and Vernier Caliper, namely specimen treatment using heating and cooling treatments with certain temperatures or temperatures. The parameters observed include stress, strain, initial diameter and final diameter. The research was carried out in the workshop laboratory of the Faculty of Agriculture, Muhammadiyah Mataram University and the Mechanical Engineering Laboratory, Mataram University. The data obtained were analysed mathematically. The test results showed that carbon steel experienced an increase in stress at a peak point of 350 N/mm2 and broke at a point of 250 N/mm2 at a strain of 31%.